2021
DOI: 10.1177/1063293x20985539
|View full text |Cite
|
Sign up to set email alerts
|

Individualized and accurate eco-design knowledge push for designers: a CAD-based feedback knowledge push method for the eco-design

Abstract: In the conceptual design phase of eco-products, the evaluation of products eco-design is often considered by designers after determining the design scheme. In order to improve the eco-design efficiency, a CAD-based feedback knowledge push method was proposed to meet the designer’s eco-design knowledge requirements. Combine with the designer knowledge background, classified eco-design knowledge, and decomposed design tasks, eco-design knowledge requirements of designers can be obtained. Based on the cosine simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The authors concluded that to avoid a slowdown of this transition, it is necessary for both people and companies to internalise the competitive advantages and business benefits that a circular economy can bring. Zhang et al [24] proposed a knowledge feedback methodology based on CAD systems to make it easier for designers to find prior eco-design knowledge that meets the requirements of the new designs they are developing. In this way, when a designer is assigned a new eco-design area, an algorithm shows similar solutions to the problem posed and facilitates adapting the solution to the new design while providing further feedback into the system.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The authors concluded that to avoid a slowdown of this transition, it is necessary for both people and companies to internalise the competitive advantages and business benefits that a circular economy can bring. Zhang et al [24] proposed a knowledge feedback methodology based on CAD systems to make it easier for designers to find prior eco-design knowledge that meets the requirements of the new designs they are developing. In this way, when a designer is assigned a new eco-design area, an algorithm shows similar solutions to the problem posed and facilitates adapting the solution to the new design while providing further feedback into the system.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…In recent years, the increasing importance of environmental protection issues has focused attention on DSP. If scientific evaluation methods can be proposed, they will facilitate the objective evaluation of CE (Ghandi and Masehian, 2015; O’Shea et al, 1998; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%